A new species and new records of Cyathus (Agaricales, Basidiomycota) from a National Park in Bahia, Brazil. Issue 1 (2nd January 2021) - Góis, Jefferson S.; da Cruz, Rhudson H. S. F.; Nascimento, Pedro H. G.; Baseia, Iuri G.
ABSTRACT: Cyathus is a genus of gasteroid fungi characterised by a small fruitbody, with a cup or inverted bell shape. Distributed worldwide, the genus contains organisms that degrade organic matter, mainly decaying wood. In Brazilian northeast, there are 21 known of Cyathus, showing a huge taxonomic richness. In this study, nineteen specimens of Cyathus collected at Monte Pascoal National Park were analysed. The methodology previously proposed for the group was used and five species were identified. Cyathus julietae, C. limbatus and C. microsporus are the first records for Bahia State. Cyathus poeppigii is the first record for Monte Pascoal. Cyathus villosocarpus is a newly described species. Description, discussion and photographs of the new records and new species are provided.